2013
DOI: 10.1242/dev.091033
|View full text |Cite
|
Sign up to set email alerts
|

Cranial neural crest cells form corridors prefiguring sensory neuroblast migration

Abstract: The majority of cranial sensory neurons originate in placodes in the surface ectoderm, migrating to form ganglia that connect to the central nervous system (CNS). Interactions between inward-migrating sensory neuroblasts and emigrant cranial neural crest cells (NCCs) play a role in coordinating this process, but how the relationship between these two cell populations is established is not clear. Here, we demonstrate that NCCs generate corridors delineating the path of migratory neuroblasts between the placode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 34 publications
4
50
0
Order By: Relevance
“…Examining image planes through the CV nerve in non-ablated control embryos at HH17 reveals a sheath of NCC enveloping the CV neurons similar to that observed in mouse, consistent with recent similar studies (Freter et al, 2013). In non-ablated control embryos NCC surround the CV nerve forming a corridor from the anterior otic vesicle to the hindbrain (Fig 6D-F).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Examining image planes through the CV nerve in non-ablated control embryos at HH17 reveals a sheath of NCC enveloping the CV neurons similar to that observed in mouse, consistent with recent similar studies (Freter et al, 2013). In non-ablated control embryos NCC surround the CV nerve forming a corridor from the anterior otic vesicle to the hindbrain (Fig 6D-F).…”
Section: Resultssupporting
confidence: 89%
“…Molecularly blocking Semaphorin/Neuropilin signaling in chick disrupts NCC migratory pathways and impairs the inward movement of epibranchial placodal neurons (Osborne et al, 2005). In some studies ablation of NCC migration by physical or molecular methods in chick results in reduced numbers of neuroblasts migrating from epibranchial ganglia and abnormal projection of central axons (Begbie and Graham, 2001; Freter et al, 2013; Yntema, 1944), although other studies reported NCC removal did not disrupt formation of ganglia (Begbie et al, 1999). In zebrafish also elimination of specific sub-populations of cranial NCC disrupts formation of the epibranchial nerves (Culbertson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3.9 Blentic et al 2011 ;Freter et al 2013 ) and strongly suggest a common evolutionary origin. Thus, the entire amphioxus ectoderm would be the equivalent of the pan-placodal ectoderm of vertebrates.…”
Section: Neural Crest and Placodesmentioning
confidence: 94%
“…Close proximity between the two cell types has been shown in a number of studies at several stages of gangliogenesis (for instance, see Begbie, 2001;Shiau et al, 2008;Shigetani et al, 2008;Theveneau et al, 2013), the most recent one reporting the intriguing observation that NCC form corridors that wrap around migrating epibranchial neuroblasts in chick and mouse (Freter et al, 2013). Contradictory results were obtained from cell ablation experiments attempting to unravel a functional interaction between the two cell populations.…”
Section: Cellular Interactions and Molecular Cues Interaction Betweenmentioning
confidence: 97%